2024
DOI: 10.1302/0301-620x.106b1.bjj-2023-0467.r1
|View full text |Cite
|
Sign up to set email alerts
|

Wait-and-scan: an alternative for curettage in atypical cartilaginous tumours of the long bones

Claire H. J. Scholte,
Desirée M. J. Dorleijn,
Duco T. Krijvenaar
et al.

Abstract: AimsDue to its indolent clinical behaviour, the treatment paradigm of atypical cartilaginous tumours (ACTs) in the long bones is slowly shifting from intralesional resection (curettage) and local adjuvants, towards active surveillance through wait-and-scan follow-up. In this retrospective cohort study performed in a tertiary referral centre, we studied the natural behaviour of ACT lesions by active surveillance with MRI. Clinical symptoms were not considered in the surveillance programme.MethodsThe aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The early diagnosis of DDCS before treatment is important to improve patient prognosis [10]. The dedifferentiation rate of atypical cartilaginous tumors has been reported to be 4-6% [47,48]. Studies have reported medium-term follow-up safety for atypical cartilaginous tumors of the long bone with active surveillance [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The early diagnosis of DDCS before treatment is important to improve patient prognosis [10]. The dedifferentiation rate of atypical cartilaginous tumors has been reported to be 4-6% [47,48]. Studies have reported medium-term follow-up safety for atypical cartilaginous tumors of the long bone with active surveillance [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%